Interactome networks and human disease - Vidal, Marc (Henry Stewart Talks, 2014)
Linear genotype-phenotype relations, Genotype and phenotype of eye color, Complex genotype-to-phenotype relationships, Cells as complex wiring diagrams of interaction, Types and properties of interactome networks, Network properties required for biological functions, Interactome mapping, Edgotype, Why systematic maps of interactome networks are important